Reflecting on Hospitality Students’ Cognitive Diversity Impact on Service Quality and Organizational Performance Standards: A Case-Study in Cy Seasonal Hotels - Michael Anastasiou (Institut Pariwisata dan Bisnis Internasional, 2020)
This study examines the impact of hospitality students’ cognitive diversity style on service quality and performance standards in seasonal hotels. A survey research method approach was implemented through a quantitative examination of a purposeful sample, collected from three-, four-, and five-star seasonal hotels in Cyprus. The survey was administered face-to-face to 316 students and 93 managers. For hypotheses testing, the Cognitive Style Inventory was adapted. Study results reveal students’ educational preparedness, professional reliability, and the positive impact of their cognitive diversity style on service quality and organizational performance standards in seasonal hotels. While students offer a diversified pool of potential candidates to successfully fulfil qualified and skilful required vacancies, a twofold requirement emerges. First is the introversion requirement related to the curriculum design of hospitality educational institutions. Second is the extroversion requirement, which sees the responsibility of seasonal hotel managers, as future employers, to be linked and guided on students’ cognitive style development via an intuitive collaboration with local hospitality educational institutions.